Optimisation Of Recycled High Density Polyethylene Pellet As Aggregate Replacement For Road Pavement - Wan Mohd Nazmi, Wan Abdul Rahman; A. F. A., Wahab; Fadzil, Mat Yahaya (Malaysian Technical Universities Network (MTUN), 2014)
The objective of this study is to investigate the optimum usage recycled high density polyethylene (HDPE) as aggregate replacement in modified asphalt. The modified asphalts were evaluated by engineering properties of asphalt such as stiffness, permanent deformation and fatigue behaviour.The aggregate substitution with recycled HDPE in asphalt ranges from 5% to 25% of asphalt with sieve size from 3.36 mm to 1.18 mm and optimum bitumen content including the hot mix asphalt wearing course 14 in standard specification of road work in Malaysia. The repeated load axial test, indirect tensile stiffness modulus test and indirect tensile fatigue test were used to evaluate the permanent deformation, stiffness and fatigue properties of asphalt, respectively. The density-void analysis indicates that the optimum bitumen content is 5.5% of weight of bitumen content. The obtained results shown that the HDPE modified asphalt could enhance the stiffness of asphalt at 15% and 20% aggregate replacement. This asphalt modification also improves permanent deformation at 1800 cycles. Finally, the HDPE modified asphalt also increase fatigue life of asphalt except 5% aggregate replacement. Therefore, the HDPE modified asphalt found suitable to used for road pavement in term of environmental and economical aspects.